Multifunctional properties of microwave assisted CdO–NiO–ZnO mixed metal oxide nanocomposite: enhanced photocatalytic and antibacterial activities - Karthik, K.; Dhanuskodi, S.; Gobinath, C.; Prabukumar, S.; Sivaramakrishnan, S. (Journal of materials science. Materials in electronics, 2018)
A facile approach for the preparation of CdO–NiO–ZnO mixed metal oxide nanocomposite was demonstrated by microwave assisted method and characterized by XRD, SEM with EDS and FTIR. XRD exhibits CdO (cubic), NiO (cubic), ZnO (hexagonal) structure with an average crystallite size of 37, 23 and 20 nm respectively. The lattice strain and the dislocation density are evaluated by W–H method. SEM and TEM images reveal the morphology as sheet like structure and FTIR indicates the characteristic stretching frequency as Cd–O (687 cm −1 ), Ni–O (865 cm −1 ) and Zn–O (472 cm −1 ). From the UV–Vis spectra, the bandgap is estimated as 2.75 eV. The fluorescence spectrum shows the emission of blue–violet (455 nm), green (524 nm) and red (678 nm). The prepared nanocomposite acts as an excellent photocatalyst for the removal of methylene blue dye under sun light irradiation. Furthermore, the antibacterial activity for concentrations (25, 50, 75 and 100 µg/mL) was carried out in-vitro against gram negative (G − Ve) i.e. Escherichia coli, Pseudomonas aeruginosa, proteus mirablis, Aeromonas hydrophila, Salmonella typhi and Vibrio cholerae ; gram positive bacteria (G + Ve): Staphylococcus aureus, Rhodococcus rhodochrous and Bacillus subtilis . Confocal laser scanning microscopy confirms the rupture of the bacterial cell wall.